Genomic basis and functional characterization of the exopolysaccharide production by a thermotolerant Bacillus isolated from Tolhuaca hot spring - Meza, Cynthia; Sepulveda, Benjamin; Flores-Castañón, Nicolás; Valenzuela, Francisca; Ormeño, Catherine; Castillo, Alexis; Echeverría-Vega, Alex; Jasem Mohammed Breig, Sura; Alardhi, Saja Mohsen; Gonzalez, Alex; Mora-Lagos, Bárbara; Banerjee, Aparna (Frontiers in Microbiology, 2025)
Bacillus licheniformis Tol1, a thermotolerant bacterial strain isolated from the Tolhuaca hot spring in Chile, was investigated for its genomic features and the functional properties of its exopolysaccharide (EPS). The whole-genome sequencing revealed ∼4.25 Mbp genome with a GC content of 45.9% and a rich repertoire of genes associated with environmental stress adaptation, antibiotic resistance, sporulation, biofilm formation, and EPS biosynthesis, including the presence of epsD and epsC. The strain also harbored intact prophage elements and a Type I-A CRISPR-Cas system, indicating potential horizontal gene transfer and genome plasticity. Confocal microscopy revealed robust biofilm formation at 45–55°C under neutral to slightly alkaline pH, with strong EPS matrix development. EPS production was optimized using OFAT and Response Surface Methodology (RSM), achieving a yield of 2.11 g L−1 under optimized conditions, which was further validated using an Artificial Neural Network (ANN) model (R2 = 0.9909). The EPS exhibited promising antioxidant activity and significant emulsification potential across various vegetable oils, which were comparable or superior to commercial bacterial EPS xanthan gum. Notably, the EPS also showed cytotoxic effects against AGS gastric adenocarcinoma cells, reducing viability by 38.38 and 37% at 50–100 μg μL−1 concentrations, respectively, suggesting potential anticancer activity. Altogether, the study highlights B. licheniformis Tol1 as a multifunctional thermophile with valuable biotechnological potential, particularly for applications in food, pharmaceutical, and biomedical industries.